2021
DOI: 10.1002/cb.1918
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of consumers' cross‐channel switching intentions: A push‐pull‐mooring approach

Abstract: This research develops and tests a model on cross‐channel switching intentions using the PPM framework. Four hundred and fifty‐six valid responses were collected from online and in‐person survey. The proposed relationships were tested using structural equation modelling. The results confirmed the positive influence of push (extent of external information search) and pull (alternative attractiveness) factors on switching intention in the cross‐channel context. The study also showed that higher multichannel self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 121 publications
0
18
0
Order By: Relevance
“…Consumers may desire to control their choices in the shape of empowerment and perceive more shopping benefits over an integrated channel, both of which generate more consumer patronage (Goraya et al, 2022). Haridasan et al (2021) reported that cross-channel switching intentions are significantly influenced by the extent of information search and alternative attractiveness. Likewise, Flavi an et al (2020) reported that webrooming leads to higher personal attribution than showrooming.…”
Section: Showrooming and Webrooming As Outcomes Of Rsbmentioning
confidence: 99%
See 3 more Smart Citations
“…Consumers may desire to control their choices in the shape of empowerment and perceive more shopping benefits over an integrated channel, both of which generate more consumer patronage (Goraya et al, 2022). Haridasan et al (2021) reported that cross-channel switching intentions are significantly influenced by the extent of information search and alternative attractiveness. Likewise, Flavi an et al (2020) reported that webrooming leads to higher personal attribution than showrooming.…”
Section: Showrooming and Webrooming As Outcomes Of Rsbmentioning
confidence: 99%
“…, 2022). Haridasan et al. (2021) reported that cross-channel switching intentions are significantly influenced by the extent of information search and alternative attractiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…It pointed out that cross-channel behavior often originates from factors beyond the control of consumers such as planning, compulsion, or opportunism, while these factors are often controllable within the control of retailers [31]. Through the push-pull-mooring approach, Haridasan et al [32] confirmed that in the cross-channel context, the push (the degree of external information search) and pull (alternative attraction) factors have a positive impact on the channel switching intentions. Yang et al [33] build a research model integrating perceived value theory and the technology acceptance model to examine the influence of the features of O2O commerce on consumer use intention.…”
Section: Literature Reviewmentioning
confidence: 99%